2018
DOI: 10.1503/cmaj.170588
|View full text |Cite
|
Sign up to set email alerts
|

Patient, family and provider experiences with transfers from intensive care unit to hospital ward: a multicentre qualitative study

Abstract: BACKGROUND: Transfer of patient care from an intensive care unit (ICU) to a hospital ward is often challenging, high risk and inefficient. We assessed patient and provider perspectives on barriers and facilitators to high-quality transfers and recommendations to improve the transfer process. METHODS:We conducted semi structured interviews of participants from a multicentre prospective cohort study of ICU transfers conducted at 10 hospitals across Canada. We purposively sampled 1 patient, 1 family member of a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 34 publications
3
61
0
1
Order By: Relevance
“…33,35 A recent qualitative study of perceived barriers and facilitators to high-quality transfer practices reported that ICU providers, ward providers, and patients and families all recommended the use of both communication tools (e.g., standardized written summary of patient course and treatment plan) and employing multimodal communication practices (i.e., verbal, written, electronic) to document the transfer to ensure continuity of care. 36 This was further echoed in our study, with both administrator groups identifying an opportunity to improve transfer practices by providing patients and families with more information and engaging them in the transfer process (e.g., shared decision-making). This reflects growing efforts in healthcare to engage relevant stakeholders including patients in research, quality improvement, and healthcare service planning.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…33,35 A recent qualitative study of perceived barriers and facilitators to high-quality transfer practices reported that ICU providers, ward providers, and patients and families all recommended the use of both communication tools (e.g., standardized written summary of patient course and treatment plan) and employing multimodal communication practices (i.e., verbal, written, electronic) to document the transfer to ensure continuity of care. 36 This was further echoed in our study, with both administrator groups identifying an opportunity to improve transfer practices by providing patients and families with more information and engaging them in the transfer process (e.g., shared decision-making). This reflects growing efforts in healthcare to engage relevant stakeholders including patients in research, quality improvement, and healthcare service planning.…”
Section: Discussionmentioning
confidence: 51%
“…While the lens through which administrators view transfers of care is likely different than that of frontline providers (e.g., physicians, nurses), the perspectives were similar with those communicated by frontline providers, patients, and family members in other steps of our research program. 8,36,45 Second, the two surveys were not distributed concurrently because the ward administrator sampling frame was derived from the survey responses of ICU administrators. We acknowledge that it is possible, although unlikely, that institutions may have substantially modified transfer polices during this 1-year time period.…”
Section: Discussionmentioning
confidence: 99%
“…In a qualitative study, patients reported a feeling of communication breakdown during transfers resulting in a perception of worsened care and difficulty in adjustment. 18,19 Limiting unnecessary relocations by ensuring an appropriate initial ED disposition may decrease patient distress and reduce the risk of medical errors during patient handoffs.…”
Section: Discussionmentioning
confidence: 99%
“…To make this judgement, ICU nurses and physicians were highly dependent of families. Family members need reassurance and information both while in the ICU (26,27) and during transition to the ward (28,29).…”
Section: Discussionmentioning
confidence: 99%